PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA STAFF BIRO PEGAWAI UNIVERSITAS ISLAM NEGERI (UIN) RADEN INTAN LAMPUNG - Wahidah, Nur Rachmah; Andhani, Destian; Sunarto, Ading (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of job satisfaction and work motivation partially and simultaneously on the performance of bureau staff at the Raden Intan State Islamic University (UIN) Lampung. The research method used is an associative quantitative approach, the population in this study is the staff of the Raden Intan Lampung State Islamic University (UIN) bureau with a total sample of 83 people, while data collection is done by distributing questionnaires to 83 respondents and then analyzed using validity tests. , reliability test, classical assumption test, regression test, coefficient, determination, correlation, and hypothesis testing (t test and f test). The results showed that job satisfaction (X1) had a positive and significant effect on the performance of Raden Intan's employees (UIN) during the Covid-19 pandemic in Bandar Lampung where the value of tcount > ttable was 18,587 > 1,990 with a significance value < 0.05, meaning that the variable satisfaction work has a partial effect on employee performance. Work motivation (X2) does not have a positive influence on employee performance (Y) Raden Intan State Islamic University (UIN) Lampung where the value of tcount < ttable is -0.856 <1.990 with a significance value of > 0.05, meaning that the work motivation variable partially affects employee performance. . Job satisfaction (X1) and work motivation (X2) simultaneously have a positive and significant effect on employee performance (Y) Raden Intan Lampung State Islamic University (UIN) where the fcount > ftable is 170.623 > 3.11 with a significance value < 0, 05 means that the variables of job satisfaction and work motivation have a simultaneous effect on employee performance.